Deadman's Castle - Lawrence, Iain, 1955- (Margaret Ferguson Books/Holiday House, 2021)
"12-year-old Igor and his family have been on the run from the sinister figure he calls The Lizard Man for as long as he can remember and he wishes that they could just live a normal life"--